Genotype Variations and Association between PAI-1 Promoter Region (4G/5G and -844G/A) and Susceptibility to Acute Myocardial Infarction and Chronic Stable Angina - Sunil Kumar; Amit Kumar Verma; Vinay Sagar; Ravi Ranjan; Rahul Sharma; Preeti Tomar; Deepti Bhatt; Yamini Goyal; Mohammed A. Alsahli; Ahmad Almatroudi; Saleh A. Almatroodi; Arshad Husain Rahmani; et al. (Cardiology Research and Practice)
The present study aimed at investigating the 4G/5G and -844G/A polymorphisms and plasma concentration of PAI-1 in patients with acute myocardial infarction (AMI) and chronic stable angina (CSA) in Indian population. It included 100 patients with AMI and stable angina and 100 healthy controls. All study subjects were typed for two PAI polymorphisms (4G/5G and -844G/A) through PCR-RFLP and level of PAI through ELISA. The comparison of AMI and CSA independently with control in terms of PAI-1 level was statistically significant but not between AMI and CSA. The frequency of 4G/4G and 4G/5G genotype and 4G allele was significantly higher in AMI cases than in control and was found to increase the risk of AMI. There was a significant relationship between 4G/5G polymorphism and AMI risk under the dominant and codominant genotype. The frequency of 4G/4G genotype and 4G allele was significantly higher in CSA cases than in control group and increases the risk of CSA. There was no significant association between 4G/5G polymorphism and CSA risk under recessive, dominant, and codominant models. The genotype and allelic frequencies difference between the cases (AMI and CSA) and control with regard to -844G/A polymorphisms were statistically nonsignificant. Also, we did not detect any significant association of -844G/A polymorphism with AMI and CSA in recessive, dominant, and codominant models. Along with the traditional risk factors, the 4G/5G allele polymorphism is an independent risk factor for the development of AMI. The detection of 4G/5G allele may therefore be helpful in primary prevention. Patients who carry the 4G/5G allele polymorphism have high concentrations of PAI-1, which might be involved in incidents leading to AMI. The present study for the first time revealed significant association of 4G/5G allele polymorphism with high risk of AMI in Indian population and will be helpful in identifying the genetic risk factors associated with AMI and CSA and for better management of diagnostic measures.